An Analysis of Human Resource Accounting in Some IT Companies - Goel, Priya; Banerjee, S. (Prabandhan: Indian Journal of Management, 2010)
A knowledge-intensive company leverages know-how, innovation and reputation to achieve success in the marketplace. Hence, these attributes should be measured and improved upon year after year to ensure continual success. Managing a knowledge organization necessitates a focus on the critical issues of organizational adaption, survival, and competence in the face of ever-increasing, discontinuous environmental change. The profitability of a knowledge firm depends on its ability to leverage the learn ability of its professionals, and to enhance the reusability of their knowledge and expertise. The intangible assets of a company include its brand, its ability to attract, develop and nurture a cadre of competent professionals, and its ability to attract and retain marquee clients. The intangible assets of a company can be classified into four major categories: human resources, Intellectual Property assets, internal assets and external assets. Human resources represent the collective expertise, innovation, leadership, entrepreneurship and managerial skills of the employees of an organization. Intellectual Property assets include know-how, copyrights, patents, products and tools that are owned by a corporation. These assets are value based on their commercial potential. A corporation can derive its revenues from licensing these assets to outside users. Internal assets are systems, technologies, methodologies, processes and tools that are specific to an organization.